White spot lesion in self-ligating versus conventional ligating bracket systems: A systematic review - Mohammad I Idris; Ahmad S Burhan; Mohammad Y Hajeer; Ahmad M Alhamwi; Fehmie R Nawaya (Journal of International Medical Research)
Background White spot lesion formation around orthodontic brackets is a major complication associated with fixed orthodontic treatment. Objective This review aimed to evaluate the current evidence regarding the differences in white spot lesion formation between self-ligating and conventional ligating brackets. Methods Eleven bibliographic databases were searched until January 2025. This review covered parallel-group and split-mouth randomized controlled trials, controlled clinical trials, and cross-sectional studies that investigated the differences in white spot lesion formation between self-ligating and conventional ligating brackets. Results Three randomized controlled trials, one controlled clinical trial, and one cross-sectional study were included in this systematic review. Among these, three studies were classified as having a low risk of bias. Four of the five included studies showed no statistically significant difference in white spot lesion formation between the two types of bracket systems (p < 0.05). Conclusion There are no potential differences in white spot lesion formation between self-ligating and conventional ligating bracket systems. However, orthodontists must be aware of the other factors affecting white spot lesion formation, with oral hygiene being the most critical factor. Registration: The protocol was registered in the PROSPERO database (CRD42022353478) on 25 August 2022.